2009
DOI: 10.1016/j.hrthm.2009.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiology of cardiac dyssynchrony and resynchronization

Abstract: Cardiac resynchronization therapy (CRT) represents the major new advance for the treatment of heart failure since the new millennium. With this therapy, failing hearts with discoordinate contraction due to conduction delay are subjected to bi-ventricular stimulation to “resynchronize” contraction and improve chamber function. Remarkably, CRT was mostly developed and tested in patients first, and the speed at which the concept became translated to an approved clinical therapy was unusually quick. To date, CRT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…One of the key mechanisms of benefit from CRT is to correct mechanical dyssynchrony [3,4]. However, in order to restore mechanical dyssynchrony, dyssynchronous segments must be viable in order to recruit their "wasted work" toward cardiac output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the key mechanisms of benefit from CRT is to correct mechanical dyssynchrony [3,4]. However, in order to restore mechanical dyssynchrony, dyssynchronous segments must be viable in order to recruit their "wasted work" toward cardiac output.…”
Section: Discussionmentioning
confidence: 99%
“…Correcting mechanical dyssynchrony within the left ventricular (LV) was proposed as one of the key mechanisms of benefit from CRT [3,4]. However, the PROSPECT trial demonstrated that no single echocardiographic measurement of dyssynchrony may be recommended to improve patient selection for CRT [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are some epidemiological studies that provide evidence of a worse outcome in a population affected with LBBB [2]. Perhaps in this case biventricular depolarization will prevent mechanical dyssynchrony and in the future an evolution to a dilated cardiomyopathy by ventricular remodeling [3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, there have been efforts to "reverse-engineer" CRT, exploring the cellular and molecular mechanisms that are involved. Indeed, dyssynchrony and resynchronization therapy induce a wide range of changes beyond the mechanical effects, many which are unique to both the disease and the treatment [15][16][17][18][19]. Interestingly, in some instances, CRT does not simply reverse the damage done by dyssynchrony, but acts in entirely novel ways to improve function.…”
Section: Author Manuscriptmentioning
confidence: 99%